Hubungan Nitrit dengan Kejadian Infeksi Saluran Kemih (ISK) pada Ibu Hamil di Rumah Sakit - Kusumawati, Erna; Istiana, Siti; Sari, Indah Mustika (Faletehan Health Journal, 2024)
Urinary tract infections (UTI) among women are increasing at a higher rate than men. The overall incidence of UTI during pregnancy is approximately 8% and can cause serious illness for the mother and baby. One of the diagnostic tests used to diagnose UTI is the urine dipstick test which can detect the presence of leukocyte etrase and can be used as an indicator of pyuria and nitrite. The conversion of nitrates to nitrites only occurs when the urine contains bacteria. The aim of the research was to examine the relationship between nitrites and the incidence of UTI among pregnant women. This research was a correlational analytical quantitative study with a retrospective approach and cross-sectional design. The sample size was 47 pregnant women diagnosed with UTI. The data was taken from patients’ medical records. The data analysis used chi square test. The results showed a relationship between nitrite levels and the incidence of UTI among pregnant women with a p value of 0.042. Asymptomatic bacteriuria is one of the reasons why a routine urinalysis is recommended in antenatal examinations of low-risk pregnant women. A diagnostic test by a urine test should be employed to confirm the diagnosis of UTI since it can detect the presence of nitrites as an indicator of bacteriuria.